Cash Circulation in the Planned Economies of Eastern Europe - Baracs, J. (Review of Economic Studies, 1959)
Journal Article Cash Circulation in the Planned Economies of Eastern Europe Get access J. Baracs J. Baracs London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 1, October 1959, Pages 50–57, https://doi.org/10.2307/2296050 Published: 01 October 1959